Effect of psychomotor intervention with the participation of a caretaker on the gesture communication of a child with autism - Taboada-Huarcaya, Xiomara (2019)
We present the case of a 3-year-old girl with autism that showed difficulties to stablish relationships and to integrate facial and body gestures to her verbal language. In addition, she showed inflexibility to postural changes and strong bond to inanimate objects. A new intervention tool was offered based on providing affection and movement through primary relationships. The objective was to facilitate motor gesture to achieve gesture communication integrated to verbal language favoring spontaneous connection of the girl with her caretaker and with her surroundings.